An Analysis Of Teacher’s Questioning Strategy During The Classroom Interaction At SMA Negeri 14 MBD - Laicerewy, Thabita Dorkas; Ferdinandus, Marcy; Meyer, Fredi (Koli Journal : English Language Education, 2022)
This research aimed to investigate the questioning techniques employed by teachers during English language instruction and to analyze the purposes served by these questions in classroom interactions. The study utilized a descriptive qualitative method with an English teacher from SMA NEGERI 14 Southwest Maluku (MBD) as the sole participant, selected through purposive sampling. Data collection involved observations and interviews. Analysis revealed various questioning strategies used by the teacher. Furthermore, the study identified that teacher questions were intended to generate interest and curiosity about the topic, promote active learning, encourage students to ask questions, assess comprehension, gather information, and maintain classroom control. In conclusion, this research underscores teachers' dedicated use of questioning techniques to gauge student understanding during English instruction sessions.